Streptomyces salinarius sp. nov., an actinomycete isolated from solar saltern soil - Klanbut, Khanungkan; Rattanakavil, Thitiya; Duangupama, Thitikorn; Suriyachadkun, Chanwit; Herron, Paul Robert; Thawai, Chitti (My University, 2023)
An actinobacterium, designated strain SS06011T, was isolated from solar saltern soil collected from Samut Sakhon province, Thailand. The taxonomic position of this strain was established using the polyphasic taxonomic approach. The strain produced grey aerial spore mass on International Streptomyces Project 2 seawater agar that differentiated into spiral spore chains with rugose-surfaced spores. Strain SS06011T was found to have ll-diaminopimelic acid in the cell peptidoglycan. Whole-cell hydrolysates contained galactose, glucose and ribose. MK-9(H6 ) and MK-9(H4 ) were major menaquinones. The major cellular fatty acids comprised iso-C16: 0, anteiso-C15: 0 and anteiso-C17: 0 . Diphosphatidylglycerol, phosphatidylethanolamine, phosphatidyl-glycerol and phosphatidylinositol were detected in cells. These characteristics were coincident with the typical morphological and chemotaxonomic properties of the genus Streptomyces. The taxonomic affiliation at the genus level of this strain could also be confirmed by its 16S rRNA gene sequence data. Strain SS06011T showed the highest 16S rRNA gene sequence similarity to Streptomyces ardesiacus NRRL B-1773T (99.1 %), Streptomyces coelicoflavus NBRC 15399T (99.1 %) and Streptomyces hyderabadensis OU-40T (99.1 %). Digital DNA–DNA hybridization (dDDH), average nucleotide identity-blast (ANIb) and average amino acid identity (AAI) values between strain SS06011T and its closely related type strains, S. ardesiacus NBRC 15402T, S. coe-licoflavus NBRC 15399T and S. hyderabadensis JCM 17657T, were in the range of 45.4–48.4 % (for dDDH), 90.8–91.9 % (for ANIb) and 90.8–91.7 % (for AAI), respectively, which are lower than the cut-off criteria for species delineation. The DNA G+C content of genomic DNA was 71.9 mol%. With the differences in physiological, biochemical and genotypic data, strain SS06011T could be discriminated from its closest neighbours. Thus, strain SS06011T should be recognized as representing a novel species of the genus Streptomyces, for which the name Streptomyces salinarius sp. nov. is proposed. The type strain is SS06011T (=TBRC 9951T=NBRC 113998T).
Keywords: 16S rRNA gene; solar saltern soil; Streptomyces; whole-genome analysis